Physicians’ knowledge and practice attitudes toward infective endocarditis antibiotic prophylaxis guidelines in Saudi Arabia - Abdullah Nasser Alhuzaimi; Abdulrahman Mohamed Bahkley; Ahmed Mohammed Aljadeed; Abdullah Abdlatif Alghaiheb (Journal of the Saudi Heart Association, 2019)
Objectives: To assess the physicians’ knowledge and practice attitudes toward the infective endocarditis antibiotics prophylaxis guidelines in Saudi Arabia. Moreover, to determine whether there is knowledge-to-practice discrepancy. Methods: A cross-sectional study was performed using a self-administered questionnaire. A questionnaire was distributed among physicians dealing with congenital heart disease patients in Saudi Arabia, from January 7, 2016 to August 30, 2016. The questionnaire designed to calculate three scores: a knowledge score, a practice score, and a knowledge-to-practice discrepancy score. A t test was used for a mean comparison between the three scores and a Pearson correlation coefficient for correlation. Results: A total of 121 physicians completed the survey. The respondents were predominantly pediatric cardiologists (84%). The mean knowledge score for infective endocarditis prophylaxis in various cardiac lesions was 8.6 ± 3.2 SD out of 14, and the mean practice score was 7.6 ± 3 SD out of 14. The mean discrepancy score was 1.1 ± 3 SD. There was a positive significant correlation between knowledge and discrepancy scores, r = 0.533, n = 121, p = 0.001, using Pearson correlation analysis. Almost 39% of our population had a discrepancy score of +1 or more. Conclusions: The knowledge about antibiotics prophylaxis of infective endocarditis in various cardiac lesions was less than optimal. Even in the presence of knowledge, there is a practice-to-knowledge discrepancy, with an overprescribing attitude for low-risk cardiac lesions that correlates significantly with more knowledgeable physicians. We recommend that physicians be up-to-date and follow the most recent guidelines. Keywords: Antibiotics prophylaxis, Congenital heart diseases, Infective endocarditis, Heart diseases